Prognostic potential of MNX1-AS1 in chemotherapy of colorectal carcinoma: MNX1-AS1 induces drug-resistance in CRC - Zhong, Guangjun; Zhou, Ming; Wang, Zhaojun; Zhu, Wansen (Cellular and Molecular Biology, 2023)
To clarify the role of MNX1-AS1 in 5-FU resistance of Colorectal carcinoma (CRC). Relative levels of MNX1-AS1 in CRC and paracancerous tissues were detected by quantitative real-time polymerase chain reaction (qRT-PCR). Recruited CRC patients were treated by 5-FU-based FOLFOX chemotherapy, and they were divided to effective group and non-effective group according to the therapeutic efficacy, followed by comparison of their differences in clinical indicators. Influences of MNX1-AS1 on clinical features of CRC were analyzed. In addition, in vitro level of MNX1-AS1 in 5-FU-resistant HCT-8 cells and their parental cells was detected. After knockdown of MNX1-AS1 in HCT-8/5-FU cells, viability change was evaluated by cell counting kit-8 (CCK-8) assay. At last, regulatory effects of MNX1-AS1 on expression levels of ABC family genes were detected. MNX1-AS1 was upregulated in CRC tissues than paracancerous ones, and its level was higher in 5-FU-resistant CRC cases in comparison to 5-FU-sensitive cases. MNX1-AS1 level was linked to tumor size, tumor differentiation, depth of invasion, TNM staging and lymphatic metastasis in CRC. Notably, TNM staging, depth of invasion and lymphatic metastasis could affect the efficacy of FOLFOX chemotherapy in CRC patients. Knockdown of MNX1-AS1 reduced viability in HCT-8/5-FU cells, and downregulated ABCA1, ABCB1, ABCC1, ABCG1 and ABCG2. MNX1-AS1 triggers 5-FU resistance in CRC cells. Knockdown of MNXK1-AS1 is conductive to the well response to FOLFOX chemotherapy in CRC patients.